Study on inhibitory activity of chitosan-based materials against biofilm producing Pseudomonas aeruginosa strains. (September 2015) - Machul, Agnieszka; Mikołajczyk, Diana; Regiel-Futyra, Anna; Heczko, Piotr B; Strus, Magdalena; Arruebo, Manuel; Stochel, Grażyna; Kyzioł, Agnieszka
Six antibiotic-resistant Pseudomonas aeruginosa strains, isolated from chronic diabetic foot infections, were chosen for studying the influence of different chitosan-based materials: chitosan solution and chitosan submicroparticles in both planktonic and 24 h-old biofilm-forming models. Chitosan solution occurred to be more effective in the reduction of bacterial populations than chitosan submicroparticles for both planktonic and biofilm-related Pseudomonas cells. It seems that the antimicrobial activity of the tested chitosan preparations depends on the individual bacterial strain susceptibility probably related to differences in the phenotypes and natural antioxidant abilities of Pseudomonas aeruginosa strains.